2020
DOI: 10.1101/2020.01.27.921460
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tomato wall-associated kinase SlWak1 acts in an Fls2- and Fls3-dependent manner to promote apoplastic immune responses toPseudomonas syringae

Abstract: Wall-associated kinases (Waks) are known to be important components of plant immunity against various pathogens including Pseudomonas syringae pv. tomato (Pst) although their molecular mechanisms are largely unknown. In tomato, SlWak1 has been implicated in immunity because its transcript abundance increases significantly in leaves after treatment with the flagellin-derived peptides flg22 and flgII-28, which activate the receptors Fls2 and Fls3, respectively. We generated two SlWak1 tomato mutants (Dwak1) usin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…In another study, it was demonstrated that wall associated kinase 1 in Solanum lycopersicum (SlWak1) plays an important role in pattern recognition receptors-triggered immunity (PTI) through transcription factor interference [32]. Recently in transcriptomic analysis, it has been found that in RP-type immune receptors regulation, EDS1, a conserved lipase like categorized as distinct subfamily known as receptor like cytoplasmic kinases (RLCKs) [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, it was demonstrated that wall associated kinase 1 in Solanum lycopersicum (SlWak1) plays an important role in pattern recognition receptors-triggered immunity (PTI) through transcription factor interference [32]. Recently in transcriptomic analysis, it has been found that in RP-type immune receptors regulation, EDS1, a conserved lipase like categorized as distinct subfamily known as receptor like cytoplasmic kinases (RLCKs) [4,6].…”
Section: Introductionmentioning
confidence: 99%